Methods of wintering yearling steers on bluestem pasture. - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The primary purpose of this study is to test the value of dry bluestem pasture as a winter feed for yearling steers fed different kinds and amounts of protein supplements.
Keywords: Beef; Bluestem pasture; Protein; Soybeanoil meal